Exogenous lipoid pneumonia due to medical aspiration of paraffin oil: a case report and literature review - Mingshuang Li; Mingshuang Li; Conglin Ren; Conglin Ren; Cangsong Chen; Cangsong Chen (Frontiers in Medicine, 2025)
This case report describes a case of exogenous lipoid pneumonia (ELP) due to medical aspiration of paraffin oil. An 87-year-old male was hospitalized with bedridden, dysphagic dysphagia. Two days after being given nasal paraffin oil, the patient developed high fever and respiratory distress. Blood gas analysis showed a PaCO2 of 33 mmHg in the room air. CT scan of the chest showed multiple ground glass opacity with solid lesions. The patient then underwent bronchoscopy, and large quantities of oily turbid fluid was found in the bronchoalveolar lavage fluid (BALF). Further cytological analysis of the BALF showed 35% phagocytes, 60% neutrophils, and 5% lymphocytes. The patient was diagnosed with ELP based on a history of paraffin oil exposure, CT imaging of the chest, and cytological examination. Despite our aggressive anti-inflammatory and anti-infective treatment, the patient eventually passed away due to advanced age and multiple complications. Aspiration of oily substances is the most important risk factor for ELP. For people at high risk of misadministration, a suitable naso-intestinal tube is more appropriate for feeding and medication.